Government Cooperation (Study of the Cooperation between the Central and Regional Governments in the Development of Tourism Priority Destinations in Tanjung Kelayang, Bangka Belitung) - Ramadhani Berthi; Tri Sulistyaningsih; Khrishno Hadi (Journal of Local Government Issues (LOGOS), 2018)
In order to improve and develop the priority sector, namely the tourism sector, 10 (ten) priority destinations are determined in Indonesia, one of them is Tanjung Kelayang Destination in Bangka Belitung. The development of this priority destination, being the domain of authority of the central government and regional governments, it is necessary for Government Cooperation. The results of the study found that the model of cooperation between the central and regional governments in the development of Tanjung Kelayang Destinations was not only developed through government cooperation in the status of KSPN (National Tourism Strategic Area) which was deconcentrated, but also developed through government cooperation in the status of KEK (Creative Economic Zone) in the concept ABCGM (Academics, Business, Community, Government, Media). In each model of cooperation in its implementation there are still some problems, namely the local government is less able to take advantage of the opportunities in proposing activities to the central government through the Deconcentration Fund and DAK (Special Allocation Funds) in the KSPN status, and there are some activities that are not focused and not suitable for the development of KEK Tanjung Kelayang. There are several inhibiting and supporting factors identified and influencing government cooperation, inhibiting factors in the development of Tanjung Kelayang Priority Destinations namely lack of accessibility especially transportation, lack of awareness of community tourism, lack of community creativity while supporting factors are many foreign tourists and there are famous tourist attractions (Laskar Pelangi Island). Thus, the Central and Regional Government Cooperation can conclude that it is still not enough to make the Tanjung Kelayang destination a priority destination in Indonesia.Keywords :Government Cooperation, Tourism Development, Priority Destinations